HUMANISTIC FOUNDATIONS OF FOREIGN LANGUAGE EDUCATION: THEORY AND PRACTICE - Svitlana Fedorenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The paper focuses on the theoretical analysis of psychological and pedagogic foundations of humanistic foreign language education viewed as an interrelated subject-subject system for improving the emotional and intellectual spheres of students' personal development, which is based on an attitude of interest in life in all its manifestations. Synthesising findings of ethics of care and dialogical pedagogy, humanistic foreign language education is intended to acquaint students with sociocultural knowledge accumulated by humanity; promote better self-understanding and awareness of their place and role in society; develop the ability to adequately assess the possibilities for their self-realisation; teach students to think independently and critically, and to communicate in a civilized and effective way with other people and the world at large. The study of the U.S. practical experience in this educational sphere is highlighted as well. The paper outlines pedagogical participatory techniques, such as role-playing and discussion. They effectively combine the humanistic approach to the educational process with the foreign language study, providing self-discovery and self-perfection. Students are trained as informed and competent interlocutors in the foreign language. They are also educated to reflect on the world through the lens of another culture. The research shows that humanistic foreign language education with its emphasis on the inner world of the learners, their individual thoughts, emotions and feelings is of great significance in overall personality development. Humanistic foundations of pedagogical participatory techniques involve students' affective experiences reflected in the values and ideals that they hold most dear, the meaning and purpose of their lives, their connectedness to each other and to the surrounding world.